The influence of human blaming or bragging behaviour towards software agent sincerity implementation - Jaafar N.H.; Ahmad M.S.; Ahmad A. (Springer Verlag, 2023)
Artificial intelligence; Autonomous agents; Distributed computer systems; Philosophical aspects; Blaming; Bragging; Designing agents; Sincerity; Software agent technology; Software agents